Molecular Targets for Treating Cognitive Dysfunction in Schizophrenia - Gray, John A. (Oxford University Press, 2007)
Cognitive impairment is a core feature of schizophrenia as deficits are present in the majority of patients, frequently precede the onset of other positive symptoms, persist even with successful treatment of positive symptoms, and account for a significant portion of functional impairment in schizophrenia. While the atypical antipsychotics have produced incremental improvements in the cognitive function of patients with schizophrenia, overall treatment remains inadequate. In recent years, there has been an increased interest in developing novel strategies for treating the cognitive deficits in schizophrenia, focusing on ameliorating impairments in working memory, attention, and social cognition. Here we review various molecular targets that are actively being explored for potential drug discovery efforts in schizophrenia and cognition. These molecular targets include dopamine receptors in the prefrontal cortex, nicotinic and muscarinic acetylcholine receptors, the glutamatergic excitatory synapse, various serotonin receptors, and the γ-aminobutyric acid (GABA) system.